Mixed media moral distinctions in advertising, public relations, and journalism - Bivins, Thomas H. (Thomas Harvey) 1947- (Routledge, 2018)
"Mixed Media offers students of journalism, advertising, and public relations the tools for making ethical and moral decisions within their professional disciplines. Covering both ethical theory and its practical application to the media professions, Mixed Media serves as an indispensable starting point for those seeking to develop an ethical framework with regard to mass media. Each media industry is covered with specific attention paid to relevant ethical decision-making approaches involving primary concerns such as truth telling, constituent obligations, persuasion versus advocacy, and respect for the consumers of public communication. In addition, the book covers new media and how ethics affect such concepts as social media, word-of-mouth advertising, and the impact of the digital revolution. And, new to this edition, recent concerns in areas such as satire and the dilemma of free speech virus constraint are discussed, as well as the quandry of native advertising in journalism. Readers will come away with a greater appreciation for moral philosophy and theory as a foundation for decision making, and will develop a personal "yardstick" by which to measure their decisions."--Provided by publisher.